Psoriasis in pregnancy: challenges and solutions - Vena GA; Cassano N; Bellia G; Colombo D (Dove Medical Press, 2015)
Gino Antonio Vena,1 Nicoletta Cassano,1 Gilberto Bellia,2 Delia Colombo,2 1Dermatology and Venereology Private Practice, Bari and Barletta, 2Novartis Farma SpA, Origgio, Varese, Italy Abstract: The available information about the effects of pregnancy on psoriasis and those of psoriasis on pregnancy is almost limited, despite the high frequency of the disease in the general population, as well as in women in reproductive years. Considering the existing evidence, pregnancy does not tend to have a negative influence on psoriasis, as in most women who experience a change in the severity and course of their psoriasis during pregnancy, the change is more likely to be reported as an improvement. This assumption can be applied more convincingly to plaque-type psoriasis, while an exception may be represented by generalized pustular psoriasis, which has been somehow linked to impetigo herpetiformis. Conflicting findings emerged from the few available studies that explored the effect of psoriasis on pregnancy outcomes. Recent studies found an association between moderate-to-severe psoriasis and some pregnancy complications, including pregnancy-induced hypertensive diseases, and have emphasized a trend toward a newborn with low birth weight in patients with psoriasis, especially in those suffering from severe forms. The safety profile during pregnancy is not completely known for many drugs used to treat psoriasis. Moisturizers and low- to moderate-potency topical steroids or ultraviolet B phototherapy represent the first-line therapy for pregnant patients. Many dermatologists may, however, recommend discontinuing all drugs during pregnancy, in consideration of medico-legal issues, and also taking into account that common forms of psoriasis do not compromise the maternal and fetal health. Anyway, for those women whose psoriasis improves during pregnancy, the interruption of any therapy for psoriasis can be a reasonable strategy. The objective of this paper was to review the most relevant literature data on psoriasis in pregnancy, trying to give concurrently practical information about clinical and prognostic aspects, as well as counseling and management. Keywords: psoriasis, pregnancy, treatment, management, outcome, topical/systemic drugs, phototherapy